PENGARUH MODIFIKASI TEPUNG JAGUNG PRAGELATINISASI TERHADAP KUALITAS COOKIES - Susilawati BS, Susilawati BS; Syam, Husain; Fadilah, Ratnawaty (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to determine the effect of pragelatinization temperature modification on corn flour quality, and to determine the effect of modified pragelatinized corn flour and the level of consumer acceptance of corn cookies. This research is an experiment research with Completely Randomized Design (RAL). This research is done through two stages. The first stage of making corn flour pragelatinization uses three steaming time. The second stage is the making of corn cookies. The variables observed were analysis of proksimat levels corn flour pragelatinization and corn cookies, starch levels analysis, amylose levels analysis, and hedonic test. The data were processed using SPSS program version 22, with variance analysis method (ANOVA) and continued with DMRT test (Duncan) at level 5%. The results showed corn flour pragelatinization 30 minutes is the best treatment to proceed to the manufacture of cookies products. The result of hedonic test of cookies as a whole is accepted by consumers, especially the comparison treatment of 70% corn flour pragelatinization and 30% wheat flour as the best treatment with water levels of 3.22%, ash levels of 1.20%, protein levels 6.33%, 12.25 % fat levels, and carbohydrates 77%. Overall, proximate analysis, starch levels, and amylosa levels of pragelatinization corn flour and corn cookies have met the established quality requirements.